A survey of early health effects of the Eyjafjallajökull 2010 eruption in Iceland: a population-based study. Issue 2 (8th March 2012) - Carlsen, Hanne Krage; Gislason, Thorarinn; Benediktsdottir, Bryndis; Kolbeinsson, Thorir Bjorn; Hauksdottir, Arna; Thorsteinsson, Throstur; Briem, Haraldur
Abstract : Objective: To estimate physical and mental health effects of the Eyjafjallajökull volcanic eruption on nearby residents. Design: Cross-sectional study. Setting: The Icelandic volcano Eyjafjallajökull erupted on 14 April 2010. The eruption lasted for about 6 weeks and was explosive, ejecting some 8 million tons of fine particles into the atmosphere. Due to prevailing winds, the ash spread mostly to the south and south-east, first over the rural region to the south, later over the Atlantic Ocean and Europe, closing European air space for several days. Participants: Residents (n=207) of the most ash-exposed rural area south and east of the volcano. Methods: The study period was from 31 May to 11 June 2010. Participants were examined by a physician. To ascertain respiratory health, standardised spirometry was performed before and after the use of a bronchodilator. All adult participants answered questionnaires about mental and physical health, their children's health and the use of protective equipment. Results: Every other adult participant reported irritation in eyes and upper airway when exposed to volcanic ash. Adults (n=26) and children (n=5) with pre-existing asthma frequently reported worsening of their symptoms. No serious health problems requiring hospitalisation could be attributed to the eruption. The majority of the participants reported no abnormal physical or mental symptoms to the examining physician. Compared to an age- and gender-matched reference group, the ash-exposed participants reported lower smoking rates and were less likely to have ventilation impairment. Less than 10% of the participants reported symptoms of stress, anxiety or depression. Conclusions: Short-term ash exposure was associated with upper airway irritation symptoms and exacerbation of pre-existing asthma but did not contribute to serious health problems. The exposure did not impair respiratory function compared to controls. Outdoor use of protective glasses and face masks was considered protective against irritation in eyes and upper airway.